Nasal high‐flow therapy compared with non‐invasive ventilation in COPD patients with chronic respiratory failure: A randomized controlled cross‐over trial. Issue 11 (13th May 2019) - McKinstry, Steven; Singer, Joseph; Baarsma, Jan Pieter; Weatherall, Mark; Beasley, Richard; Fingleton, James
ABSTRACT: Background and objective: Non‐invasive ventilation (NIV) is part of the standard of care for hypercapnic respiratory failure secondary to COPD, but may be poorly tolerated. Preliminary evidence suggests nasal high‐flow (NHF) therapy may improve hypercapnia in COPD and be well tolerated. We compared NHF and NIV in people with COPD and chronic hypercapnic respiratory failure. Methods: Single‐blind randomized controlled two‐way cross‐over single‐centre trial was conducted in New Zealand. Twenty‐four participants with stable hypercapnic COPD received: NHF at 45 L/min and NIV at 15/4 cm H2 O, each for 60 min with a 15‐min washout in between. The primary outcome was transcutaneous partial pressure of carbon dioxide (PtCO2 ) at 60 min, adjusted for baseline. Results: NIV reduced the PtCO2 more than NHF (mean (SD) at 60 min by −5.3 (5.0) vs −2.5 (3.5) mm Hg; difference: −2.8 (−5.0 to −0.5) P = 0.021). Difference across all time points was −2.5 mm Hg (95% CI −4.5 to −0.5, P = 0.016). There was no significant difference in the proportion of participants with a reduction of PtCO2  ≥ 4 or ≥ 8 mm Hg. Participants rated NHF significantly better for ease of application, comfort and fit. Conclusion: In stable COPD patients with chronic hypercapnia, NIV resulted in a greater reduction in PtCO2 compared with NHF, which was of uncertain clinical significance. NHF was better tolerated than NIV and may be a therapeutic option for some people with hypercapnic respiratory failure.Clinical Trial Registration: ACTRN12616001701415 atwww.anzctr.org.au Abstract : Non‐invasive ventilation (NIV) reduces transcutaneous partial pressure of carbon dioxide (PtCO2 ) more than nasal high‐flow (NHF) therapy in hypercapnic COPD, but NHF is better tolerated. See related Editorial